Affective Tendencies of Science Teachers in Teaching Socioscientific Issues - Meryem Hatun Elbahan; Haluk Elbahan; Burcu Anilan (Mimbar Sekolah Dasar, 2022)
This study aims at identifying the intrinsic affective tendencies of science teachers in teaching socioscientific issues (SSI) based on different variables and their personal perspectives. The participants of the study consisted of 394 science teachers who taught at public schools during the 2021 and 2022 academic years. Regarding the research method, a mixed method that combined quantitative and qualitative research methods was employed in this study. Quantitatively, the "Affective Tendency Scale for Teaching Socioscientific Issues” comprising four dimensions and 28 items was applied to 394 science teachers. Meanwhile, qualitatively, semi-structured interviews were conducted with six science teachers from the total participant teachers who volunteered to take part. Subsequently, for statistical operations in this study, the SPSS program was utilized to analyze the quantitative and qualitative data in a descriptive manner. Conclusively, the results revealed that science teachers' affective tendencies in teaching SSI (Socioscientific Issues) were high on both quantitative and qualitative levels.